Evaluation of the Reality of Foreign Reserves in Iraq and the Role of the Central Bank in Managing them for the Period (2004 – 2024) - Nooradeen Aziz, Rebaz; Rasul Younis, Yasin (Iraqi Journal for Administrative Sciences, 2025)
This research analyzes and evaluates the state of foreign reserves in Iraq. It focuses on the Central Bank of Iraq’s (CBI) role in managing them for the period 2004–2024. The analysis considers structural, political, economic, and security challenges impacting Iraq’s monetary and financial stability. The study adopts a descriptive-analytical approach and uses quantitative data to assess reserve adequacy based on international standards. These include import coverage and the ratio of reserves to M2, external debt, and GDP. The findings reveal that Iraq managed to accumulate significant reserves during certain periods, especially after the CBI gained independence and oil revenues surged. However, reliance on oil made reserves vulnerable to external shocks. Despite improvements in reserve adequacy, structural reforms remain essential to ensure sustainability and diversify foreign exchange sources. The study recommends diversifying the economy, strengthening reserve management, enhancing central bank independence, and improving coordination with fiscal policy.